Weather Forecast and Weather Based Agromet Advisories - Vashisth, Ananta; Singh, Ravender (Indian Farming, 2015)
Accuracy of forecast of weather parameters was observed to be useful to farmers for doing appropriate field operations and management practices depending on suitability of weather conditions particularly for newly released high yielding varieties of various crops. Application of agromet advisory bulletin based on current and forecasted weather is useful for land preparation, sowing time, amount and time for irrigation, agricultural operations and management of pest and diseases in different crops. Farmers received weather forecast based agroadvisories including optimum use of inputs for different farm operations. Due to judicious and timely utilization of inputs, cost of production for the farmers reduced. At the same time yields level of the farmers increased by doing proper crop management in time. The increased yield level and reduced cost of production, led to increased net returns for farmers. Thus the application of agromet advisory bulletin based on current and forecasted weather is useful tool for enhancing the production and income by reducing the farm input cost.